Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ta00397d
|View full text |Cite
|
Sign up to set email alerts
|

Interior design of three-dimensional CuO ordered architectures with enhanced performance for supercapacitors

Abstract: 3D ordered nanostructures assembled by 1D and 2D CuO building blocks dramatically improve the electrochemical performance for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 61 publications
3
69
1
Order By: Relevance
“…Figure 1 a shows the schematic of the synthesis of MO, CO, and CMO@MCO (details described in the Experimental Section ). The reaction mechanism for the formation of MO by reacting MnCl 2 with NaOH can be described as follows 43 while the reaction mechanism for the synthesis of CO by reacting CuCl 2 with NaOH can be presented as follows 44 During the synthesis of CMO@MCO, Cu 2+ and Mn 2+/3+ can be doped into MO and CO, respectively, in three different ways: (I) substitution of Mn 2+/3+ by Cu 2+ in MO and the substitution of Cu 2+ by Mn 2+/3+ in CO, (II) bonding with oxygen, and (III) as a secondary phase. 40 Figure 1 b displays the X-ray diffraction (XRD) patterns of as-prepared MO, CO, and CMO@MCO together with the simulated XRD patterns of MO and CO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 a shows the schematic of the synthesis of MO, CO, and CMO@MCO (details described in the Experimental Section ). The reaction mechanism for the formation of MO by reacting MnCl 2 with NaOH can be described as follows 43 while the reaction mechanism for the synthesis of CO by reacting CuCl 2 with NaOH can be presented as follows 44 During the synthesis of CMO@MCO, Cu 2+ and Mn 2+/3+ can be doped into MO and CO, respectively, in three different ways: (I) substitution of Mn 2+/3+ by Cu 2+ in MO and the substitution of Cu 2+ by Mn 2+/3+ in CO, (II) bonding with oxygen, and (III) as a secondary phase. 40 Figure 1 b displays the X-ray diffraction (XRD) patterns of as-prepared MO, CO, and CMO@MCO together with the simulated XRD patterns of MO and CO.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of well-defined redox peak in both CO and CMO@MCO can be ascribed to the involvement of the redox reaction between Cu 2+ and Cu + according to the following reaction ( reaction 9 ). 44 Moreover, the intercalation/deintercalation of K + into the tunnels of CO ( Figure S8 ) and CMO@MCO and the redox reaction of the Cu 2+ dopants ( reaction 10 ) 42 in CMO@MCO are also contributing in the energy storage process. The discharge current density of all of the electrodes showed a linear behavior with the scan rates ( Figure 5 c), demonstrating a faster charge–discharge (CD) process with good reversibility.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is worth mentioning that the shapes of building blocks play an important role in achieving good electrochemical performances. By designing different 3D ordered CuO nanostructures assembled by building blocks through a solvothermal method, Zheng and co‐workers found that the 3D ordered CuO nanoflowers exhibited higher capacitance, better rate performance and longer cycle lifetime, compared to disorganized CuO nanoflakes and 3D ordered CuO nanourchins . The better electrochemical performance can be attributed to the high specific surface areas, good electron and ion mobility, and high mechanical and structural stability derived from the well‐arranged building blocks on the surface.…”
Section: D Hierarchically Nanostructured Materialsmentioning
confidence: 99%
“…Aiming at combining the merits of each single component and coupling with some extraordinary properties while possessing high exposed area, the construction of 3D hierarchical structure is to integrate one‐dimensional or two‐dimensional nanomaterials as building blocks with levels ranging from nanometers to macroscopic sizes. To this end, prominent effort has been contributed to the development of 3D hierarchical structures and various morphologies including spheres, nanoflakes, nanosheets, nanoflowers, have been built for carbonaceous materials, layered double hydroxides, transition mental oxides/sulfides and so on. Owing to the combination of multifunctional materials and their unique structures, the asymmetric supercapacitors based on 3D hierarchically nanostructured materials manifest high capacitance, good rate capability and stable cyclic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among different NPs, those composed by copper oxide (CuO) have gained much scientific attention for its nontoxic and abundant component elements, with multiple applications in supercapacitors, Li‐ion batteries, sensor devices, wet catalysis, photothermal catalysis, and hole transport materials for perovskite and organic solar cells . Described 3D CuO systems can be either nonporous well‐defined clusters or mesoporous aggregates of NPs obtained by the ordered fusion of nanosized building units .…”
Section: Introductionmentioning
confidence: 99%